A sterile chitin conduit for nerve repair and method of making same
Patent Information
- Application Number
- CN202510883698.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-06-29
AI Technical Summary
[0013]本发明的目的在于提供一种包含无菌甲壳质导管的神经修复产品及其制备方法,以解决现有技术中遇水或组织液时软化,机械性能缺失,无法提供对结缔组织入侵神经段端起物理屏障作用等问题,同时在缝合性能、降解性能方面得到明显提升,临床使用便捷,且本发明选择的材料适用于神经修复,不增加新溶剂,无化学试剂残留问题
[0030] (1) This invention is the first to use moist heat sterilization to sterilize catheter products, which preserves the microporous mesh structure of the product without affecting its performance and achieves sterility. Traditional EO sterilization or irradiation sterilization will destroy the microstructure of polymer materials, while this technology, through precise control of temperature and pressure parameters, ensures zero damage to the three-dimensional microporous mesh of 1-60um inside the catheter during the sterilization process, ensuring that the biomechanical environment required for nerve cell adhesion is completely preserved.
Smart Images

Figure CN120679001B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical device technology, and in particular to a sterile chitin catheter for nerve repair and its preparation method. Background Technology
[0002] Repairing peripheral nerve injuries is a challenging medical problem. Autologous nerve transplantation, due to its non-immunogenic effects, is considered the "gold standard" for peripheral nerve repair. However, it also faces challenges such as limited donor tissue supply, the risk of neuroma formation, size mismatch, and axonal distribution between the donor nerve and the injury site. Nerve conduits are tubular devices made of natural and / or synthetic polymers. The severed nerve ends are placed inside the conduit and sutured, allowing nerve axons to grow along the lumen. Nerve conduits provide a physical barrier against connective tissue intrusion into the nerve segment, preventing scarring; they also promote the accumulation of neurotrophic factors, guiding axial axonal growth and reducing neuroma formation; and they utilize distal nerve chemotaxis to repair longer peripheral nerve defects. However, currently, poor biocompatibility, low bioactivity, and poor mechanical properties are the main drawbacks of most artificial nerve conduits. For example, polyglycolic acid (PEG), a synthetic material, possesses excellent mechanical properties and rapidly degrades into lactic acid within three months. It was the first artificial nerve conduit approved by the U.S. Food and Drug Administration (FDA). However, it may degrade before peripheral nerve regeneration, and its degradation product, lactic acid, may be toxic to peripheral nerve regeneration. Polycaprolactone (PVC) nerve conduits are another FDA-approved artificial nerve conduit. Their advantage is that they produce fewer acidic products during degradation, theoretically resulting in lower toxicity to surrounding tissues. However, their high rigidity and lack of flexibility make them more difficult to handle clinically, and they also have a higher complication rate. Biomaterials such as collagen-based nerve conduits have good biocompatibility, but their poor mechanical properties make it difficult to maintain the necessary space during nerve repair.
[0003] Among numerous tissue-engineered neural conduit materials, chitin and chitosan exhibit significant advantages in biocompatibility and degradability, each with its own strengths and weaknesses. Chitosan, obtained by deacetylation of chitin, has significantly higher solubility than natural chitin, facilitating the removal of coexisting impurities and making it easier to process and shape. Chitin, on the other hand, has advantages in degradation rate and mechanical properties, but natural chitin has poor solubility and is difficult to process. Studies suggest that chitin and chitosan may be relatively ideal tissue engineering materials.
[0004] For example, Chinese patent CN 114533967A discloses a deacetylated chitosan nerve conduit, which achieves different degradation cycles by controlling the porosity of the nerve conduit and the degree of deacetylation of the raw material chitosan. However, its mechanical properties are poor, and it cannot provide a physical barrier against connective tissue invading the nerve segment. Another example is Chinese patent CN 1411873A, which discloses an absorbable artificial biological cannula for guiding and promoting effective nerve regeneration and its preparation method. This conduit is made from chitosan as raw material, formed by hollow fiber spinning and stretching, and loaded with nerve growth factors. However, after loading with nerve growth factors, it is formed by freeze-drying. The product will soften and lose its mechanical properties when exposed to water or tissue fluid.
[0005] For example, Chinese patent CN 111001039A discloses a nerve injury repair material and its preparation method. The method involves mixing collagen and chitosan into a solution, shaping it, freeze-drying it into tubes, and then sterilizing it with ethylene oxide gas to maintain sterility. This product is used in the field of medical device manufacturing and can be used for nerve injury repair. However, it still needs to be used in a dry state; it softens when exposed to water or tissue fluid, loses its mechanical properties, and cannot provide a physical barrier against connective tissue intrusion into the nerve segment.
[0006] The existing technology has the following technical problems:
[0007] 1) Existing products generally use EO sterilization. Although sterilization can achieve sterility, EO residue is common. In addition, some products use irradiation sterilization. Although irradiation can achieve sterility, it will damage the microstructure of the product. Some products add protective solution during irradiation. Such protective solution is usually an organic solvent and needs to be cleaned before surgery, which increases the surgical procedure.
[0008] 2) During nerve repair and suturing surgery, it is difficult to avoid the product getting wet (contact with tissue fluid or water during the operation). Existing products generally soften when wet and cannot maintain their shape, serving only to prevent adhesion. They cannot provide a stable repair microspace for nerve repair and their efficacy cannot meet clinical expectations.
[0009] 3) Nerve repair requires a certain period of time. It generally takes about 3 months for proximal regenerated nerves to regenerate to the target organ and restore to optimal function. Implanted nerve repair products generally need to maintain a relatively complete shape, toughness and strength within 3-6 months. Existing technology products are mainly collagen products or polymer synthetic products. The former degrades too quickly, while the latter degrades too slowly.
[0010] 4) Existing technology products are usually prepared by molding, which fails to effectively form a microporous network structure suitable for cell adhesion.
[0011] 5) Existing technology products lack sufficient toughness and cannot return to their natural shape after compression, thus failing to meet clinical use requirements.
[0012] Based on this, the present invention provides a nerve repair product comprising sterile chitinous ducts and a method for preparing the same to solve the above-mentioned technical problems. Summary of the Invention
[0013] The purpose of this invention is to provide a nerve repair product comprising sterile chitinous conduits and its preparation method, thereby solving the problems of softening upon contact with water or tissue fluid, loss of mechanical properties, and inability to provide a physical barrier against connective tissue intrusion into the nerve segment in existing technologies. Simultaneously, it significantly improves suture performance and degradation performance, is convenient for clinical use, and the materials selected in this invention are suitable for nerve repair, do not introduce new solvents, and have no chemical reagent residue issues. This invention is achieved through the following technical solutions:
[0014] This invention discloses a sterile chitin catheter for nerve repair. The product comprises a sterile chitin catheter, which is treated with moist heat sterilization technology. Its surface is smooth and transparent, and it is a hollow tube with an inner diameter of 0.5-8 mm and a wall thickness of 0.5-2 mm. The tube arm is solid, and the inner surface exhibits a microporous mesh structure with pore sizes ranging from 1-60 μm. The catheter has good water resistance; its dimensions and mechanical properties remain unchanged when immersed in water for injection or purified water.
[0015] As a further improvement, the catheter described in this invention is obtained by moist heat sterilization, and the Fo value of moist heat sterilization is greater than or equal to 8.
[0016] As a further improvement, the axial tensile strength of the catheter described in this invention is 20 to 60 N, and the radial compressive strength is 2 to 12 N.
[0017] As a further improvement, the degree of acetylation of the catheter described in this invention is 70% to 95%. The catheter has good flexibility and can quickly return to its original shape after being bent.
[0018] This invention also discloses a method for preparing a sterile chitin catheter for nerve repair, comprising the following steps:
[0019] 1) Preparation of soluble chitosan: Chitin powder was placed in sodium hydroxide solution and stirred to react. After the reaction solution was drained, the solid was washed until neutral and then dried to obtain soluble chitosan.
[0020] 2) Preparation and filling: Dissolve the above soluble chitosan in glacial acetic acid solution. After complete dissolution, fill the solution into a specific mold, let it stand to defoam, and obtain the filled product.
[0021] 3) Freeze-drying: Transfer the above-mentioned filled products to a freeze-drying chamber for freeze-drying to obtain freeze-dried products;
[0022] 4) Cleaning: Take out the freeze-dried product, place it in a special cleaning rack, neutralize it with alkali solution first, and then clean it with purified water or water for injection until neutral. Drain the waste liquid to obtain the cleaned sample.
[0023] 5) Chitinization: Place the washing sample into an acetic anhydride ethanol solution and react for 1-4 hours. After draining the reaction solution, the reaction sample is obtained.
[0024] 6) Secondary cleaning: The reaction sample is neutralized with alkaline solution and then washed with purified water or water for injection until neutral. The cleaning solution is drained to obtain the finished product to be sterilized.
[0025] 7) Packaging and sterilization: Place the prepared product to be sterilized into an aluminum foil bag, add more than 2 ml of purified water or water for injection, seal the bag, and perform moist heat sterilization to obtain the final product.
[0026] As a further improvement, in step 1) of the present invention, the mass fraction of the sodium hydroxide solution during the preparation of soluble chitosan is 50% ± 5%, the reaction time is 4-8 hours, and the reaction temperature is 110-160℃; the viscosity-average molecular weight of the prepared soluble chitosan is 700,000-1,700,000, and the concentration of the prepared soluble chitosan for formulation is 3-4%.
[0027] As a further improvement, in step 2) of the present invention, the pre-freezing temperature during freeze-drying is -10 to -30°C, and the temperature during primary drying is -1 to -6°C.
[0028] As a further improvement, the concentration of the acetic anhydride ethanol solution during chitinization in step 5) of this invention is 5-30%. The nerve repair product containing sterile chitin ducts provided by this invention allows the chitin ducts to be directly removed for nerve repair, and they will not deform or swell upon contact with tissue fluid, nor will they lose mechanical strength or toughness.
[0029] Based on this, the present invention has the following advantages compared with existing methods and published patents:
[0030] (1) This invention is the first to use moist heat sterilization to sterilize catheter products, which preserves the microporous mesh structure of the product without affecting its performance and achieves sterility. Traditional EO sterilization or irradiation sterilization will destroy the microstructure of polymer materials, while this technology, through precise control of temperature and pressure parameters, ensures zero damage to the three-dimensional microporous mesh of 1-60um inside the catheter during the sterilization process, ensuring that the biomechanical environment required for nerve cell adhesion is completely preserved.
[0031] (2) The nerve repair product of the present invention uses chitosan with a molecular weight of 700,000 to 1,700,000, which can withstand moist heat sterilization and can be taken out and used directly without any other treatment, making it convenient for surgical operation.
[0032] (3) This invention is the first to use soluble chitosan reverse acetylation to prepare a chitinous nerve cannula with high acetylation degree. It has a short degradation cycle, can be rapidly degraded after nerve recovery and repair, has good biocompatibility, and improves the patient experience.
[0033] (4) The nerve repair product of the present invention uses a suitable freeze-drying process, namely, a pre-freezing temperature of -10℃ to -30℃ and a first drying temperature of -1 to -6℃. The crystals are controlled within a suitable size range by slow freezing and crystallization. Then, the solution water is removed by drying and sublimation to form a three-dimensional honeycomb structure, thereby forming a microporous network structure of suitable size on the inner surface, which is conducive to nerve cell adhesion and accelerates nerve injury repair. At the same time, the nerve repair product of the present invention uses a suitable chitinization (acetylation) process, namely, the concentration of acetic anhydride ethanol solution is 5-30%, and the reaction time is 1-4 hours, thereby cross-linking the tube (tube wall) into a solid and obtaining tube strength, which can effectively resist external extrusion deformation.
[0034] (5) The nerve repair product of the present invention has good mechanical properties and can maintain its original size and mechanical properties after contact with tissue fluid or water during surgery, providing a stable repair microspace for nerve repair and accelerating nerve trauma repair.
[0035] (6) The nerve repair product of the present invention has good flexibility and can quickly return to its original shape after being bent or squeezed, which is beneficial to the suturing operation of the surgery, shortens the operation time, and improves the success rate of the surgery.
[0036] (7) The nerve repair product of the present invention has good appearance and transparency, which facilitates intraoperative operation and observation. Attached Figure Description
[0037] Figure 1 This is a diagram of the chitinous vessel structure in Example 1;
[0038] Figure 2 This is a scanning electron microscope longitudinal section image of the chitinous vessels;
[0039] Figure 3 Scanning electron microscope image of the inner surface of chitinous ducts;
[0040] Figure 4 Tissue staining images at 1 week and 4 weeks after chitin implantation into muscle;
[0041] Figure 5 HE staining comparison of epineurial suture (left) and chitinous duct suture (right);
[0042] Figure 6 A comparison of Glasgow Coma stained images of epineurial suture (left) and chitinous duct suture (right). Detailed Implementation
[0043] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0044] Example 1: Preparation of a 2mm*10mm sterile chitin catheter.
[0045] Raw materials: 50g chitin powder, 1000g 50% sodium hydroxide aqueous solution, 960ml 2% glacial acetic acid aqueous solution, 18L 15% acetic anhydride ethanol solution.
[0046] Steps: Add 50g of chitin powder to 1000g of 50% sodium hydroxide aqueous solution, heat at 150℃ for 4 hours. After the reaction is complete, remove the reaction waste liquid and wash with water until neutral. After drying, soluble chitosan is obtained. Dissolve 40g of chitosan in 960ml of 2% glacial acetic acid aqueous solution, stir until completely dissolved, and pour into a special mold with a specification of 2mm*10mm. Let it stand until no visible bubbles are visible. Then transfer the above mold to a freeze dryer for freeze drying. Set the pre-freezing temperature to -15℃ and the pre-freezing time to 800min. Set the temperature for the first drying to -3℃ and the drying time to 1600min. After freeze-drying, the sample was removed from the mold and placed in a cleaning rack. It was then soaked in 5% NaOH aqueous solution for 30 minutes, rinsed with water for injection until neutral, and then reacted with 15% acetic anhydride ethanol solution for 3 hours. After soaking in 10% NaOH aqueous solution overnight, it was rinsed with water for injection until neutral and then lengthened to 10 mm to obtain a chitinous catheter with a specification of 2 mm * 10 mm. The catheter was placed in an aluminum foil bag, 3 ml of water for injection was added, and the bag was sealed and sterilized by moist heat. F0 = 12 was set to obtain a sterile chitinous catheter.
[0047] Sterile chitin duct performance testing
[0048] The sterile chitin catheter prepared using the method in Example 1 was first observed under a magnifying glass. The catheter was found to be clean, white, and transparent in appearance, with uniform dimensions: an inner diameter of 2.0 mm and a length of 10 mm. (See [link to example 1]). Figure 1 Secondly, scanning electron microscopy revealed micropores on its inner surface, which participate in... Figure 3 The pipe body (longitudinal section) is thick; see [reference]. Figure 2 .
[0049] This invention tested the tensile strength, radial compressive strength, swelling properties, and degree of acetylation of sterilized chitin catheters. The tensile strength and radial compressive strength of the catheters were tested using an electronic universal testing machine; the swelling properties were tested using specialized measuring instruments.
[0050] Tensile strength testing: The tensile strength of the conduit was tested using an electronic universal testing machine. The process is as follows:
[0051] Take 3 tubing samples and fix both ends of the samples to the clamps of the push-pull tester. Carefully ensure that the samples are not stretched, twisted or damaged by the clamps, and keep them in a natural state as much as possible. Stretch the samples at a constant rate of 20 mm / min until they break, and measure the load at the time of breakage.
[0052] Tests revealed that the average tensile strength was 40 N and the elongation at break was 125%.
[0053] Radial compressive strength test: The tensile strength of the conduit is tested using an electronic universal testing machine. The process is as follows:
[0054] Take 3 tubing samples and place them horizontally in the middle of the push-pull press. The press contacts the sample and presses down at a speed of 20 mm / min. The radial displacement of the tubing is half the inner diameter of the tubing. Record the pressure value measured by the push-pull press at this time.
[0055] Tests revealed that the average radial compressive strength was 4 N.
[0056] Swelling property testing: Swelling property testing is performed using specialized measuring instruments. The procedure is as follows:
[0057] Five samples of this product and two control samples (the control sample was a Tianxinfu artificial nerve sheath with a specification of φ2x10) were taken. The inner diameter, outer diameter, and length of the samples were measured using a special measuring instrument. The wall thickness was calculated by the difference between the outer diameter and the inner diameter: wall thickness = (outer diameter - inner diameter) / 2. The samples were then immersed in physiological saline for 24h±2h to allow them to fully swell. After removing the samples and absorbing the surface moisture, the inner diameter, outer diameter, and length were recorded again, and the wall thickness was calculated. The rate of change of the inner diameter, length, and wall thickness was calculated by comparing the changes in the measured values before and after immersion.
[0058] Tests revealed that the change rate of the inner diameter, length, and wall thickness of this product was less than 4%, while the reference product lost its tubular shape after full swelling.
[0059] Acetylation degree test: The acetylation degree was detected using nuclear magnetic resonance spectroscopy, and the procedure is as follows:
[0060] Prepare a NaOD D2O solution (11%), dissolve the sample at -80℃, and select D2O as the test solvent.
[0061] Tests revealed an average degree of acetylation of 76%.
[0062] Biosafety assessment of sterile chitin catheters
[0063] Two healthy adult New Zealand white rabbits were anesthetized, and three implantation points were selected at equal intervals approximately 2.5 cm on each side of the rabbit's spine to implant the sample, with each point spaced 2.5 cm apart. The sample was inserted into the muscle to a depth of 1-2 cm, and the myofascia and skin incision were sutured. The clinical manifestations of the animals were observed during the experiment. One animal was treated at 1 week and 4 weeks post-implantation to observe the lesions in the subcutaneous and muscle tissues at the implantation site.
[0064] Results: During the experiment, the rabbits showed no general abnormalities, skin wounds healed well, and no obvious redness, swelling, ulceration, or other adverse reactions were observed at the implantation site. No subcutaneous or intramuscular bleeding or suppuration was observed at 1 and 4 weeks post-implantation. Furthermore, H&E staining of the muscle tissue at the implantation site showed a small number of fibroblasts and numerous capillary proliferations in the surrounding tissue at 1 and 4 weeks post-implantation, along with significant inflammatory cell infiltration, primarily consisting of granulocytes, lymphocytes, macrophages, and multinucleated macrophages (Figure 4). Evaluation was conducted according to the scoring criteria in GB / T16886.6-2022 "Biological Evaluation of Medical Devices Part 6: Local Reaction Tests after Implantation." The local biological reaction scores at 1 and 4 weeks post-implantation were 0.00 and 0.80, respectively, both less than 2.9 points, therefore, the results were deemed non-irritating.
[0065] Sterile chitinous duct grafts for repair of peripheral nerve defects in animals
[0066] After routine induction and maintenance anesthesia of the pigs, the hair on the left upper limb was shaved and disinfected. The bilateral median nerves were severed 2 cm above the elbow. The right side was then reconnected using a peripheral nerve sheath, with a 2 mm gap between the nerve ends. The left side was sutured using a traditional epineurium. Adhesion at the nerve suture site was observed grossly 14 days post-implantation. H&E staining of the median nerve injury site was performed to observe the histopathological condition, and Fixed Blue staining was used to observe the regenerated myelin sheath.
[0067] Experimental results: 14 days post-implantation, no adhesions were observed at the nerve suture site in the animals. H&E staining showed complete nerve healing at the sheath suture site, with some sheath remnants visible. However, at the epineurium suture site, significant collagen fiber production was observed, indicating incomplete nerve healing. Figure 5 As shown in the image, Solid Blue staining revealed that the myelin sheath or myelin-encased nerve fibers at the epineurium suture site appeared blue and were fewer in number; while the myelin sheath or myelin-encased nerve fibers at the repair site of the sleeve-joint repair site appeared blue and were more numerous, indicating better repair results and significantly superior repair compared to epineurium suture. Figure 6 As shown.
[0068] Example 2: Preparation of a 6mm*10mm sterile chitin catheter.
[0069] Raw materials: 100g chitin powder, 2000g 50% sodium hydroxide aqueous solution, 1920ml 2% glacial acetic acid aqueous solution, 36L 15% acetic anhydride ethanol solution.
[0070] Steps: ① Add 100g of chitin powder to 1000g of 50% sodium hydroxide aqueous solution and heat at 110℃ for 8 hours. After the reaction is complete, remove the reaction waste liquid and wash with water until neutral. Dry the soluble chitosan. ② Dissolve 80g of chitosan in 1920ml of 2% glacial acetic acid aqueous solution and stir until completely dissolved. Pour the solution into a 6mm*10mm mold and let it stand until no visible bubbles remain. ③ Transfer the mold to a freeze dryer and freeze dry. Set the pre-freezing temperature to -25℃ and the pre-freezing time to 1600min. Set the temperature for the first drying step to -6℃ and the drying time to 3000min. ④ After freeze-drying, remove the sample from the mold, place it in a cleaning rack, soak it in 5% NaOH aqueous solution for 30 minutes, rinse it with water for injection until neutral, then add 30% acetic anhydride ethanol solution and react for 2 hours. After soaking it in 10% NaOH aqueous solution overnight, rinse it with water for injection until neutral, then cut it to 10 mm in length to obtain a chitinous catheter with a specification of 6 mm * 10 mm. ⑤ After placing it in an aluminum foil bag, add 3 ml of water for injection, seal it, and sterilize it with moist heat. Set F0 = 8 to obtain a sterile chitinous catheter.
[0071] Sterile chitin duct performance testing
[0072] The sterile chitin catheter prepared using the method of Example 2 was first observed under a magnifying glass. It was found that the prepared catheter had a clean appearance, was white and transparent, and had uniform size, with an inner diameter of 6.0 mm and a length of 10 mm.
[0073] This invention tested the tensile strength, radial compressive strength, swelling properties, and degree of acetylation of sterilized chitin catheters. The tensile strength and radial compressive strength of the catheters were tested using an electronic universal testing machine; the swelling properties were tested using specialized measuring instruments.
[0074] Tensile strength testing: The tensile strength of the conduit was tested using an electronic universal testing machine. The process is as follows:
[0075] Take 3 tubing samples and fix both ends of the samples to the clamps of the push-pull tester. Carefully ensure that the samples are not stretched, twisted or damaged by the clamps, and keep them in a natural state as much as possible. Stretch the samples at a constant rate of 20 mm / min until they break, and measure the load at the time of breakage.
[0076] Tests revealed that the average tensile strength was 56 N and the elongation at break was 138%.
[0077] Radial compressive strength test: The tensile strength of the conduit is tested using an electronic universal testing machine. The process is as follows:
[0078] Take 3 tubing samples and place them horizontally in the middle of the push-pull press. The press contacts the sample and presses down at a speed of 20 mm / min. The radial displacement of the tubing is half the inner diameter of the tubing. Record the pressure value measured by the push-pull press at this time.
[0079] Tests revealed that the average radial compressive strength was 4 N.
[0080] Swelling property testing: Swelling property testing is performed using specialized measuring instruments. The procedure is as follows:
[0081] Take 5 samples of this product and measure their inner diameter, outer diameter, and length using specialized measuring tools. Calculate the tube wall thickness using the difference between the outer diameter and the inner diameter: tube wall thickness = (outer diameter - inner diameter) / 2. Immerse each sample in physiological saline for 24h ± 2h to allow for full swelling. Remove the samples, absorb surface moisture, and record the inner diameter, outer diameter, and length again. Calculate the tube wall thickness and calculate the rate of change of inner diameter, length, and wall thickness by comparing the changes in measurements before and after immersion.
[0082] Testing revealed that the variation rate of the inner diameter, length, and wall thickness of this product is less than 4%.
[0083] Acetylation degree test: The acetylation degree was detected using nuclear magnetic resonance spectroscopy, and the procedure is as follows:
[0084] Prepare a NaOD D2O solution (11%), dissolve the sample at -80℃, and select D2O as the test solvent.
[0085] Testing revealed an average degree of acetylation of 83%.
[0086] Comparative Example 1
[0087] Chitosan was prepared at different reaction temperatures, with other parameters the same as in Example 1.
[0088] The molecular weight and solubility of the obtained chitosan are shown in the table below:
[0089] Table 1 Comparison of molecular weight and solubility of chitosan
[0090] 70℃ / Insoluble 90℃ 1832179 Soluble in 2% acetic acid, but viscous. 110℃ 1682979 2% acetic acid soluble 130℃ 1065053 2% acetic acid soluble 150℃ 879141 2% acetic acid soluble 160℃ 699657 2% acetic acid soluble
[0091] As shown in Table 1, when preparing soluble chitosan, the higher the reaction temperature, the lower the molecular weight of the prepared soluble chitosan. However, above 160℃, the molecular weight decreases significantly, which is not conducive to the subsequent preparation of conduits. Below 110℃, the molecular weight of the prepared chitosan is too high, and the prepared chitosan acetate solution is too viscous, which is not conducive to subsequent processing. Below 70℃, the prepared chitosan is insoluble and cannot proceed to the next step.
[0092] Comparative Example 2
[0093] Sterile chitosan catheters were prepared by selecting soluble chitosans with molecular weights of 1.83 million, 1.68 million, 879,000, and 700,000 from Comparative Example 1 and adding approximately 200,000 molecular weight chitosan from commercially available sources. Other parameters were the same as in Example 1.
[0094] The prepared lyophilized products are shown in Table 2 below:
[0095] Table 2 Comparison of molecular weight and freeze-dried product molding characteristics
[0096]
[0097]
[0098] As can be seen from Table 2, the molecular weight of soluble chitosan is crucial to the success of product molding, and a molecular weight between 700,000 and 1,700,000 is more suitable.
[0099] Comparative Example 3
[0100] Freeze-drying was performed at different pre-freezing temperatures, with other parameters the same as in Example 1;
[0101] The freeze-dried products obtained are shown in Table 3 below:
[0102] Table 3 Comparison of Pre-freezing Temperature and Freeze-dried Product Formation
[0103] -5℃ Not frozen -10℃ Good freeze-drying -20℃ Good freeze-drying -30℃ Good freeze-drying -40℃ The surface of the freeze-dried sample showed cracks, which appeared as vertical lines.
[0104] As can be seen from Table 3, the pre-freezing temperature during freeze-drying is crucial to the success of freeze-dried product formation, and a pre-freezing temperature of -10 to -30℃ is more suitable.
[0105] Comparative Example 4
[0106] The reaction was carried out with acetic anhydride ethanol solutions of different concentrations, and other parameters were the same as in Example 1;
[0107] The obtained reaction samples are shown in Table 4:
[0108] Table 4 Comparison of Acetic Anhydride Ethanol Solution and Reaction Samples
[0109] 2% The sample was spongy. 5% The sample is white and slightly opaque. 10% The sample is colorless and transparent. 20% The sample is colorless and transparent. 30% The sample is colorless and transparent. 40% Sample shape deformation
[0110] As can be seen from Table 4, the concentration of the acetic anhydride ethanol solution is crucial to the success of the reaction, and a concentration of 5% to 30% is more appropriate.
[0111] Comparative Example 5
[0112] Sterilization was performed using different packaging forms and sterilization methods, with other parameters the same as in Example 1;
[0113] Table 5 Comparison of different packaging forms and sterilization methods
[0114]
[0115] As shown in Table 5, the choice of sterilization method is crucial for maintaining product toughness and necessary mechanical strength (sterility can be achieved under suitable parameters). EO-sterilized products lack toughness, exhibiting excessive rigidity and unsuitable for implantation (5-1); irradiation sterilization without any protective agent also results in a lack of toughness (5-2); irradiation sterilization using purified water as a protective agent results in brittle products that crack easily upon contact (5-3 / 5-4 / 5-5); irradiation sterilization using glycerol as a protective agent, with an irradiation dose between 20-25 kGy, results in tough products (5-6 / 5-7 / 5-8); moist heat sterilization results in tough products with even higher mechanical strength. The choice of moist heat sterilization is crucial for product performance; moist heat sterilization with an F0 ≥ 8 is more suitable.
[0116] Comparative Example 6
[0117] Change the parameters according to the following conditions, and the rest is the same as in Example 2;
[0118] 6-1: ① The reaction temperature is set to 90℃;
[0119] 6-2:② The concentration of glacial acetic acid in the solution is 1%.
[0120] 6-3:③ The pre-freezing temperature is set to -35℃;
[0121] 6-4: The concentration of acetic anhydride in ④ is 40%;
[0122] 6-5:⑤ Sterilization is defined as irradiation sterilization, with glycerin protection.
[0123] Example 2 Uniform, transparent 56N 4N Toughness 6-1 White and opaque 35N <1N Lack of toughness 6-2 Uniform, transparent 56N 4N Toughness 6-3 Uneven, translucent 48N 3N Lack of toughness 6-4 Deformation, Transparency 55N Deformation direction: 2N Toughness 6-5 Yellowish, transparent 34N 3N Toughness
[0124] As can be seen from the table above, when the acetic acid is completely soluble, the concentration does not affect the product performance, and the configuration in Example 2 has the best effect.
[0125] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A sterile chitosan catheter for nerve repair, characterized in that, The catheter is treated with moist heat sterilization technology, resulting in a smooth and transparent surface. It is a hollow tube with an inner diameter of 0.5-8 mm and a wall thickness of 0.5-2 mm. The tube arms are solid, and the inner surface exhibits a microporous mesh structure with pore sizes ranging from 1-60 μm. When immersed in water for injection or purified water, the catheter maintains its dimensions and mechanical properties, with an axial tensile strength of 20-60 N, a radial compressive strength of 2-12 N, and a degree of acetylation of 70%-95%. The preparation method of the sterile chitosan catheter includes the following steps: 1) Preparation of soluble chitosan: Chitin powder is placed in a sodium hydroxide solution with a mass fraction of 50%±5% and stirred at 110-160℃ for 4-8 hours. After draining the reaction solution, the solid is washed until neutral and dried to obtain soluble chitosan with a viscosity-average molecular weight of 700,000-1,700,000. 2) Preparation and filling: Dissolve the above soluble chitosan in glacial acetic acid solution. After complete dissolution, fill the solution into a specific mold, let it stand to defoam, and obtain the filled product. 3) Freeze-drying: Transfer the filled product to a freeze-drying chamber, pre-freeze at -10 to -30°C, and dry once at -1 to -6°C to obtain the freeze-dried product; 4) Washing: Take out the freeze-dried product, place it in the washing rack, neutralize it with alkali solution first, then wash it with purified water or water for injection until neutral, drain the waste liquid, and obtain the washed sample. 5) Chitinization: Add 5-30% acetic anhydride ethanol solution to the washing sample, react for 1-4 hours, and then drain the reaction solution to obtain the reaction sample; 6) Secondary cleaning: After neutralizing the reaction sample with alkaline solution, it is then washed with purified water or water for injection until neutral, and the cleaning solution is drained to obtain the finished product to be sterilized. 7) Packaging and sterilization: Place the finished product to be sterilized into an aluminum foil bag, add more than 2ml of purified water or water for injection, seal the bag and perform moist heat sterilization. The F0 value is ≥8, and the final product is obtained.
2. A method for preparing a sterile chitin catheter for nerve repair as described in claim 1, characterized in that, Includes the following steps: 1) Preparation of soluble chitosan: Chitin powder is placed in a sodium hydroxide solution with a mass fraction of 50%±5% and stirred at 110-160℃ for 4-8 hours. After draining the reaction solution, the solid is washed until neutral and dried to obtain soluble chitosan with a viscosity-average molecular weight of 700,000-1,700,000. 2) Preparation and filling: Dissolve the above soluble chitosan in glacial acetic acid solution. After complete dissolution, fill the solution into a specific mold, let it stand to defoam, and obtain the filled product. 3) Freeze-drying: Transfer the filled product to a freeze-drying chamber, pre-freeze at -10 to -30°C, and dry once at -1 to -6°C to obtain the freeze-dried product; 4) Washing: Take out the freeze-dried product, place it in the washing rack, neutralize it with alkali solution first, then wash it with purified water or water for injection until neutral, drain the waste liquid, and obtain the washed sample. 5) Chitinization: Add 5-30% acetic anhydride ethanol solution to the washing sample, react for 1-4 hours, and then drain the reaction solution to obtain the reaction sample; 6) Secondary cleaning: After neutralizing the reaction sample with alkaline solution, wash it with purified water or water for injection until neutral, drain the cleaning solution to obtain the finished product to be sterilized; 7) Packaging and sterilization: Place the finished product to be sterilized into an aluminum foil bag, add more than 2ml of purified water or water for injection, seal the bag and perform moist heat sterilization. The F0 value is ≥8, and the final product is obtained.
Citation Information
Patent Citations
Nerve injury repair material and preparation method and application thereof
CN111001039A
Deacetylchitosan nerve conduit and preparation method thereof
CN114533967A
Partial chitosan bio-canula capable of inducing and promoting effective regeneration of nerve and its preparation method
CN1411873A